Denver's Lakeside Amusement Park: from the white city beautiful to a century of fun - Forsyth, David, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
In Denver's Lakeside Amusement Park, author David Matthew Forsyth details the history of the park, from its construction through its centennial, exploring how it has weathered a century of metropolitan growth, technological innovation, and cultural shifts.
Introduction: In search of blooming gardens -- Lakeside, an amusement enterprise -- Just take a trip out to jolly Lakeside -- Lakeside, the white city beautiful -- Keeping Lakeside's bright lights shining -- Benjamin Krasner and Lakeside's new setup -- Lakeside speedway and the roaring bugs of speed -- The wild chipmunk vs. the mouse -- The stockers take over at Lakeside speedway -- Lakeside amusement park, public nuisance? -- Lakeside, the most entertaining city in America -- Conclusion: a century of fun at Lakeside Amusement Park.
Keywords: Lakeside Amusement Park (Denver, Colo.) -- History; Denver (Colo.) -- Social life and customs